Perancangan Sistem Informasi Manajemen Toko (Point Of Sales) Berbasis Website di UMKM Hijab Nafisa - Ridho Awang Sudrajat; Enny Aryanny (Jurnal Manajemen Riset Inovasi, 2023)
Transaction management at Hijab Nafisa used to be done manually, causing errors in record keeping and periodic inventory checks, resulting in inefficient service. The author designed an information system using PHP as the programming language and MySQL as the database. This paper described the analysis and design of a store management information system (point of sales) that has successfully facilitated the transaction process and inventory checks. After that, a system test was carried out and compared with the old method of manual and ineffective information transaction processes, resulting in a proposed system that facilitated the transaction process and inventory checks. Additionally, there was also ease in data reporting that could be printed out for easy reading.